Working Mother’s Breastfeeding Experience: A Phenomenology Qualitative Approach - Raden, Natalia Damaiyanti Putri; Padeng, Eufrasia Prinata; Laput, Dionesia Octaviani (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2023)
Breast milk is a diet that satisfies all of a baby’s physical, psychological, social and spiritual needs because it contains nutrients, hormones, immunological components and growth factors. Unfortunately, many working mothers choose to stop breastfeeding due to various factors. The purpose of this study was to explore the experiences of working mothers in exclusive breastfeeding. This study used a qualitative research design with a phenomenological descriptive approach. Data were collected using in-depth interviews and then analyzed using the Colaizzi method. The study results show that children who receive exclusive breastfeeding are healthier and have adequate nutrition. However, working mothers have difficulty in breastfeeding. So, support from partners, family members, supervisors and colleagues influences a mother’s decision to breastfeed. In addition, leave regulations and child care facilities at work affect breastfeeding ability of working mothers. This study provides information about breastfeeding challenges and the support needed by breastfeeding mothers working to formulate better policies that support breastfeeding. Policies covering employee rights and privileges, such as extended maternity leave, support facilities and child care services, are critical to the success of exclusive breastfeeding by working mothers.